2017
DOI: 10.1002/ange.201703630
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Deformation Accelerates Protein Ageing

Abstract: A hallmark of tissue ageing is the irreversible oxidative modification of its proteins. We show that single proteins, kept unfolded and extended by a mechanical force, undergo accelerated ageing in times scales of minutes to days. A protein forced to be continuously unfolded completely loses its ability to contract by folding, becoming a labile polymer. Ageing rates vary among different proteins, but in all cases they lose their mechanical integrity. Random oxidative modification of cryptic side chains exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This revealed a mechanical hierarchy within the Ig domains, with proximal Ig domains (nearer to the N-terminal) having lower mechanical stability than the distal Ig domains of the I-band. Further engineering of a covalent HaloTag anchor to either the N- or C-terminus of the protein has permitted specific immobilization of recombinant titin proteins for study at high force and long durations (41, 49, 57). …”
Section: Studies Of Titin Under Forcementioning
confidence: 99%
“…This revealed a mechanical hierarchy within the Ig domains, with proximal Ig domains (nearer to the N-terminal) having lower mechanical stability than the distal Ig domains of the I-band. Further engineering of a covalent HaloTag anchor to either the N- or C-terminus of the protein has permitted specific immobilization of recombinant titin proteins for study at high force and long durations (41, 49, 57). …”
Section: Studies Of Titin Under Forcementioning
confidence: 99%
“…Direct evidence of mechanical deformation with accelerated protein ageing was recently reported by Valle-Orero et al [45] Subjecting proteins to repeated folding and unfolding was found to reduce the ability of the protein to return to the orig-inal conformation.E xtrapolating these results to enzyme chemistry meanst hat denaturation could easily occur when exposing biocatalysts to harshm echanical conditions such as the ones experienced in ball mills. An enhancement of the enzymes tabilityw as achieved through immobilization of the biocatalysts on variouss upports.…”
Section: Catalysis By Peptides and Enzymes Under Mechanochemical Condmentioning
confidence: 81%
“…The rich interplay between protein biochemistry and nanomechanics is also exemplified by the mechanical effects of disulfide isomerization, which can be trigged by mechanical force resulting in force-dependent nanomechanical modulation (Alegre-Cebollada et al 2011b ; Giganti et al 2018 ). Intriguingly, extended polypeptides age in a time scale of minutes to days losing their ability to fold (Valle-Orero et al 2017b ). Although the mechanisms behind this observation are not completely understood, it is possible that accumulating chemical modifications could contribute to the inability of the protein to refold, similar to the effects of S-glutathionylation described above.…”
Section: Modulation Of Protein Nanomechanicsmentioning
confidence: 99%